Typo/graphic days 10 - Panayides, Angelos (My University, 2026)
Typo/graphic days 10 poster and visual identity Typo/graphic days is an annual event of lectures and workshops on typography and graphic design organised by the The Semiotics and Visual Communication Lab (SVC Lab) of the Department of Multimedia and Graphic Arts, the Language and Graphic Communication Research Lab, at Cyprus University of Technology, supported by Cyprus Association of Graphic Designers and Illustrators.